Commercialization of the small farm sector and multidimensional poverty - Sylvester Ochieng Ogutu; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2018)
Global poverty rates have declined considerably, but the number of people living in extreme poverty remains high. Many of the poor are smallholder farmers. Agricultural commercialization - meaning a shift from subsistence to more market-oriented farming - can play a central role in improving smallholder welfare. Previous studies evaluated the impact of agricultural commercialization on income poverty, but whether income gains from commercialization are really used for satisfying basic needs was hardly analyzed up till now. Here, we evaluate the effect of commercialization on income poverty, as well as on the multidimensional poverty index that looks at deprivations in terms of education, nutrition, health, and other dimensions of living standard. Using data from 805 farm households in Kenya, we estimate average treatment effects. We also analyze impact heterogeneity with quantile regressions. Results show that commercialization significantly reduces both income poverty and multidimensional poverty. The magnitude of the income gains is positively correlated with income level, meaning that special market-linkage support for marginalized farms may be required to avoid rising income inequality. However, the effect in terms of reducing basic needs deprivations is strongest among the poorest households, suggesting that agricultural commercialization contributes effectively to achieving the sustainable development goals.
Keywords: C21; I32; Q12; Q13; 330; Agricultural commercialization; Welfare; Multidimensional poverty; Kenya